Opowieść o zdobyciu Konstantynopola przez uczestników czwartej wyprawy krzyżowej (6712/1204) w średniowiecznej ruskiej tradycji historiograficznej - Brzozowska, Zofia A. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2016)
The Old-Russian account about the siege of Constantinople by participants of the Fourth Crusade in 1204 has survived in several East Slavic historiographical texts and represents primarily an independent literary work. Certainly, the earliest of these texts is the Novgorod First Chronicle. It is an older edition preserved only in one copy – the so-called “Synodal manuscript”, which was written in the middle of the thirteenth century. At that time the story was written. Its author could have taken information about the events he described directly from eyewitnesses. His account of events is characterized by objectivity and credibility and constitutes a valuable resource for the study of the Fourth Crusade